Perwujudan Nilai Budaya dalam Tradisi Bedendang Melalui Aplikasi TikTok sebagai Bentuk Kearifan Lokal Bengkulu Selatan - Nurmanita, Mutiara (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2021)
The Bedendang tradition is the most important part of South Bengkulu’s customs that need to be preserved and preserved among young people. This study aims to describe and analyze the embodiment of cultural values in the Bedendang tradition through the TikTok application as a form of South Bengkulu local wisdom. The research method used is a content analysis as what and how questions through data analysis techniques to get conclusions. The results show that the TikTok application can be used as a trend to attract young people to make the Bedendang tradition the most important part of everyday life because there are cultural values that are used as local wisdom from South Bengkulu. The conclusion from this research is that TikTok is one of the most trending applications today, with photo and video based that can attract young people to love and preserve the culture of the South Bengkulu region.